2020
DOI: 10.1002/acm2.13005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a hydrogel spacer on the intrafractional prostate motion during CyberKnife treatment for prostate cancer

Abstract: The purpose of this study was to evaluate the effect of a hydrogel spacer on intrafractional prostate motion during CyberKnife treatment. The retrospective study enrolled 24 patients (with the hydrogel spacer = 12, without the hydrogel spacer = 12) with two fiducial markers. Regarding intrafractional prostate motion, the offset values (mm) of three axes (X‐axis; superior [+] to inferior [−], Y‐axis; right [+] to left [−], Z‐axis; posterior [+] to anterior [−]) obtained from fiducial markers position between a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In our study, there was no significant difference in maximum VL, whereas superior and anterior MIDs were significantly larger in the spacer group in our study, and the difference between the two groups were 0.5 mm in the superior direction and 0.7 mm in the anterior direction. Suzuki et al [32] also reported the effect of the hydrogel spacer on the intrafractional prostate motion during the CyberKnife treatment for prostate cancer. They calculated the mean intrafractional prostate motion in the SI, LR, and AP directions for each patient using two fiducial markers and kV X-ray images and compared the results of the spacer group with the non-spacer group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, there was no significant difference in maximum VL, whereas superior and anterior MIDs were significantly larger in the spacer group in our study, and the difference between the two groups were 0.5 mm in the superior direction and 0.7 mm in the anterior direction. Suzuki et al [32] also reported the effect of the hydrogel spacer on the intrafractional prostate motion during the CyberKnife treatment for prostate cancer. They calculated the mean intrafractional prostate motion in the SI, LR, and AP directions for each patient using two fiducial markers and kV X-ray images and compared the results of the spacer group with the non-spacer group.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the complications related to the injection of hydrogel spacer have been reported [27,28]. Regarding prostate motion, it was shown that the insertion of hydrogel spacer did not greatly limit interfractional and intrafractional prostate displacements [29][30][31][32][33]. We hypothesized that the hydrogel spacer potentially implicates the prostate variability during RT.…”
Section: Introductionmentioning
confidence: 93%
“…It was also reported that intra-fractional prostate motion was not affected by a hydrogel spacer in the treatment of cyberknife. 27 A similar tumor-tracking system recently became available for tomotherapy systems, potentially allowing the same margin in the treatment of SBRT for localized prostate cancer using tomotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Suzuki et al . reported that there was no effect of HS on intrafaction prostate motion in three axes during Cyberknife treatment for Japanese prostate cancer patients [ 17 ]. However, since intrafraction prostate motion may also be affected by irradiation conditions, such as preparation methods and irradiation time, strictly speaking, it is necessary to study each facility, and we are currently continuing to do that.…”
Section: Discussionmentioning
confidence: 99%